A Clockwork Orange - Kubrick, Stanley; Malcolm McDowell; Patrick Magee; Michael Bates; Warren Clarke; John Clive; Adrienne Corri; Carl Duering; Paul Farrell; Clive Francis; Michael Gover; Miriam Karlin; et al. (UK Warner Bros. Pictures, 1971)
In a futuristic Britain, a gang of teenagers go on the rampage every night, beating and raping helpless victims. After one of the boys quells an uprising in the gang, they knock him out and leave him for the police to find. He agrees to try "aversion therapy" to shorten his jail sentence. When he is eventually let out, he hates violence, but the rest of his gang members are still after him.
In the not-too-distant future, a charming young sociopath named Alex, leads a nihilistic lifestyle of 'ultraviolence' which comes to a head when he is jailed for murder and volunteers for an experimental brainwashing treatment to reform criminals in exchange for a shorter prison sentence.
Alex, a teenage hooligan in a near-future Britain, gets jailed by the police. There he volunteers as guinea pig for a new aversion therapy proposed by the government to make room in prisons for political prisoners. "Cured" of his hooliganism and released, he is rejected by his friends and relatives. Eventually nearly dying, he becomes a major embarrassment for the government, who arrange to cure him of his cure. A pivotal moment is when he and his gang break into an author's home: the book he is writing (called "A Clockwork Orange") is a plea against the use of aversion therapy, on the grounds that it turns people into Clockwork Oranges (Ourang is Malay for "Man"): they are not being good from choice (sentiments later echoed by the prison chaplain). The film reflects this: many bad scenes in a Clockwork Orange are accompanied by jolly music; if we are to experience them as we should, we have to do it consciously, by realising they are bad, and not because the director tells us so through the use of music and images.
Stomping, whomping, stealing, singing, tap-dancing, violating, Derby-topped teddy-boy hooligan Alex (Malcolm McDowell) has his own way of having a good time. He has it at the tragic expense of others. Alex's journey from amoral punk to brainwashed proper citizen forms the dynamic arc of Stanley Kubrick's future-shook vision of Anthony Burgess's novel. Unforgettable images, startling musical counterpoints, the fascinating language used by Alex and his pals - Kubrick shapes them into a shattering whole. Hugely controversial when first released, A Clockwork Orange won the New York Film Critics Best Picture and Director honors and earned four Academy Award nominations, including Best Picture. The power of its art is such that it still entices, shocks, and holds us in its grasp.
Alex, a violent juvenile in the near future, is caught after a number of brutal rapes and murders. While imprisoned, he submits to a controversial experiment to make criminals ill at the mildest suggestion of violence or conflict. Now Alex's victims want to welcome him back into society with the same enthusiasm Alex had always exhibited when performing his crimes.
Being the adventures of a young man ... who couldn't resist pretty girls ... or a bit of the old ultra-violence ... went to jail, was re-conditioned ... and came out a different young man ... or was he ?
Keywords: Crime -- American Corner; Drama; Thriller